The Determining Factors of the Change of the Quantity of Money in the Light of Traditional - بتراحنا د. ماهر (Dirasat in Economics and Business, 1982)
This study aims at recognizing the factors which determine the change in the quantity of money in the light of Socialist Banking theory. This theory assumes an economic system which depends completely on an overall planning of national activities. we know that there are two different model of such planning being applied in Marxist communities such as Soviet Union and Yugoslavia, namely, the central planning model (i.e. vertical planning approach) and the decentral planning model (i.e. horizontal planning approach). The study includes also a survey of the principal foundations of each of these models. In the light of this survey we have come to conclusion that the change in quantity of money under the central planning frame work is submitted to full and direct sort of voluntary controlling of the State Bank, and corollary, there is no need or scale for using the traditional policies of cash and credits; whereas the change in the quantity of money under the decentral planning framework is determined by two factors namely, cash and credit plans and cash and credit policies. At the end of this analysis it has been referred that there is a clear direction in the planned socialist countries toward the horizontal planning approach. This means that importance of using the cash and credit policies as a determining or controlling factor will be increasing in these countries.